Comparative Study Between Concurrent Chemoradiation and Radiation Alone in the Treatment of Advanced Head and Neck Cancer - Md. Habib; Sadia Rezvi; Julekha Khatun; Md. Karim (International Journal of Clinical Oncology and Cancer Research, 2026)
Concurrent chemoradiotherapy is an established option for suitable patients with non-metastatic head and neck squamous cell carcinoma, but evidence from resource-limited settings remains important for real-world treatment decisions. This single-centre prospective comparative study was conducted at the Department of Radiotherapy, Rajshahi Medical College Hospital, Bangladesh, from January to December 2014, comparing early treatment response and acute toxicity between concurrent chemoradiation and radiation alone. 66 patients with histologically confirmed, non-metastatic squamous cell carcinoma of the head and neck were enrolled and equally allocated to two groups. Group A received concurrent chemoradiotherapy (external beam radiotherapy, 60 Gy/30 fractions over 6 weeks, plus cisplatin 70 mg/m 2 every 3 weeks for three cycles); Group B received the same radiotherapy schedule alone. Patients were assessed weekly during treatment and 6 weeks post-treatment. Baseline T-category, nodal status and stage were broadly comparable between groups. Complete response was significantly higher with concurrent chemoradiation than radiation alone (66.7% vs 39.4%), while partial response was lower (33.3% vs 60.6%; χ 2 =4.92, p=0.048). Oral cavity tumour regression at 6 weeks was greater with concurrent chemoradiation (84.26% vs 64.39%; p=0.018), as was neck node regression (65.69% vs 41.25%; p=0.011). Among laryngeal cancer patients, complete downstaging to T0 occurred in 71.4% (Group A) versus 42.9% (Group B). Acute toxicities—nausea, vomiting, xerostomia, mucositis, and mild haematological changes—were manageable, with no grade 3/4 toxicity or treatment-related deaths. Concurrent chemoradiation produced superior early tumour response compared with radiation alone, with increased but manageable acute toxicity. Larger randomized studies with longer follow-up are warranted to evaluate survival, late toxicity, and functional outcomes.